If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(x + -15) = 0 Reorder the terms: (4 + x)(x + -15) = 0 Reorder the terms: (4 + x)(-15 + x) = 0 Multiply (4 + x) * (-15 + x) (4(-15 + x) + x(-15 + x)) = 0 ((-15 * 4 + x * 4) + x(-15 + x)) = 0 ((-60 + 4x) + x(-15 + x)) = 0 (-60 + 4x + (-15 * x + x * x)) = 0 (-60 + 4x + (-15x + x2)) = 0 Combine like terms: 4x + -15x = -11x (-60 + -11x + x2) = 0 Solving -60 + -11x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-4 + -1x)(15 + -1x) = 0Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(15 + -1x)' equal to zero and attempt to solve: Simplifying 15 + -1x = 0 Solving 15 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 0 + -15 -1x = 0 + -15 Combine like terms: 0 + -15 = -15 -1x = -15 Divide each side by '-1'. x = 15 Simplifying x = 15Solution
x = {-4, 15}
| 3ln(x-5)=1 | | 3(x-6)-4x=-10 | | 18x^3-98x=0 | | 4(2-c)-5(2c+8)=-12 | | 3x-30=45-2x | | -39=-8(h+2)+3(2h-5) | | 321+123=444 | | 3p^2+5=8 | | 6c^2+17c+2=0 | | 8(19-x)=7(3x+1) | | 7=-5x+2x | | 3a^2-13a+4=0 | | 4g-6-g=3 | | 7xg=42 | | 16-2n-5+8n=67 | | 6ln(x-8)=1 | | 90=90p-90 | | -54=-32+w | | 111=x+68 | | 147n^4-84n^2+12= | | -9+12x-10-4x=8x-6x+46+1 | | g-35=-62 | | 8x+5=3-(9x-8) | | 0+8=8 | | r+53=-19 | | m+65=11 | | -3.6l=-71+34 | | n-75=42 | | 7lnx-3=8 | | x^2+16xy+64y^2= | | y+37=59 | | 34+-71=-3.61 |